2006
DOI: 10.1177/009286150604000302
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Labels Can Triple Perceived Risk in Clinical Trials

Abstract: Presented in part at DIA 41st Annual Meeting. lune 26-30.2005. in Washington. DC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…While a previous study [12] found combined descriptors to outperform verbal descriptors, this study found less compelling support for an advantage of combined descriptors over numeric descriptors. Information in the combined format did not generally lead to more accurate side effect risk estimates than information in numeric format only, with the exception of risk perceptions about pulmonary embolism.…”
Section: Relative Accuracy Between Conditionscontrasting
confidence: 99%
See 1 more Smart Citation
“…While a previous study [12] found combined descriptors to outperform verbal descriptors, this study found less compelling support for an advantage of combined descriptors over numeric descriptors. Information in the combined format did not generally lead to more accurate side effect risk estimates than information in numeric format only, with the exception of risk perceptions about pulmonary embolism.…”
Section: Relative Accuracy Between Conditionscontrasting
confidence: 99%
“…Participants generally over-estimated the risk of side effects irrespective of the manner of presentation [see also [8,[10][11][12][13]]. Participants may not have completely trusted the information supplied in the scenario [11], or personal experiences of cancer treatment may have influenced their judgment.…”
Section: Estimations Of Side Effect Riskmentioning
confidence: 99%
“…For example in the UK expert witnesses are encouraged to use one of a small set of verbal expressions to convey probability to a jury (Association of Forensic Science Providers, 2009) despite the fact that participants associate a wide range of values with each of these expressions (Mullen, Spence, Moxey & Jamieson, 2014). Similar problems are associated with the use of verbal expressions to convey the probability of side effects on medicine labels (Berry & Hochhauser, 2006).…”
Section: Early Work On the Mapping Between Numbers And Wordsmentioning
confidence: 96%
“…This approach has been used successfully in previous research. [125][126][127] Findings broadly indicate that comprehension of the information is improved, particularly for people with low numeracy. 128 Furthermore, the same study suggested that evaluative categories can increase deliberative processing of the numerical information.…”
Section: Numerical Informationmentioning
confidence: 87%